2021
DOI: 10.1590/s1677-5538.ibju.2020.0129
|View full text |Cite
|
Sign up to set email alerts
|

Personal and familial factors associated with toilet training

Abstract: Purpose: Toilet training (TT) is an important marker in a child's physical and psychosocial development. The present study aimed to evaluate aspects associated to delayed TT. Material and Methods: We interviewed 372 parents of children who had completed TT up to 48 months before the interview. The questionnaires were applied at school exits when parents went to pick their children up and at public parks. Questions included demographics, aspects related to TT, dysfunction voiding symptom score and evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Toilet Training is an important step to support children's ability to control micturition and defecation independently. Control of elimination was carried out by the cerebral cortex which is responsible for facilitating and inhibiting the micturition reflex (Griffiths, 2015;Netto et al, 2020). To be able to perform these abilities a child needs to go through a complex process that is influenced by anatomical, physiological, and cultural factors (Carvalho et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Toilet Training is an important step to support children's ability to control micturition and defecation independently. Control of elimination was carried out by the cerebral cortex which is responsible for facilitating and inhibiting the micturition reflex (Griffiths, 2015;Netto et al, 2020). To be able to perform these abilities a child needs to go through a complex process that is influenced by anatomical, physiological, and cultural factors (Carvalho et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that maternal support has a very important role in supporting the success of TT. Mothers who provide good support, children are able to fight anxiety, can increase self-confidence, and are not afraid to do new habits (Netto et al, 2020). The role of the mother in accompanying the child to successfully carry out TT can have good benefits for the child's physical, psychological, cognitive, and emotional health development, and conversely, the low support of the mother can cause problems related to the child's development in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Enuresis has been found to be three times more likely in children who start toilet training before the age of 18 to 24 months. 27 Murillo et al 28 found no relationship between the age of starting toilet training and lower urinary tract dysfunction or constipation. Carvalho et al 29 also found no difference between the groups regarding the onset age of toilet training and occurrence of nocturnal enuresis.…”
Section: The Relationship Between Sociodemographic Features and The A...mentioning
confidence: 99%